2015
DOI: 10.1016/j.ajog.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Does the number of forceps deliveries performed in residency predict use in practice?

Abstract: OBJECTIVE We aimed to determine if a threshold number of forceps deliveries in residency predicts use of forceps in independent practice. STUDY DESIGN We surveyed Obstetrics and Gynecology residency graduates of two academic programs from 2008-12 regarding the use of operative vaginal delivery in practice. At these programs, residents are trained in both forceps and vacuums. Individual case log data were obtained with the number of forceps deliveries performed by each respondent during residency. Respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…7 Finally, Andrews et al examined the correlation between FAVD in residency and the use of forceps in independent practice at two residency programs in Colorado. 8 The authors concluded that residents who performed more than 13 FAVDs were highly likely to use forceps after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Finally, Andrews et al examined the correlation between FAVD in residency and the use of forceps in independent practice at two residency programs in Colorado. 8 The authors concluded that residents who performed more than 13 FAVDs were highly likely to use forceps after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…Andrews et al reported that performing more than 13 forceps deliveries increased the likelihood of obstetricians using the technique in practice. 6) However, as clinical application without any experience should be avoided, we feel that video learning or simulation of the forceps delivery maneuver is important. Lee et al suggested that video learning may motivate obstetricians to learn this skill.…”
Section: Discussionmentioning
confidence: 99%
“…Percent of residents planning to perform universal cystoscopy with hysterectomy postresidency based upon familiarity with published literature. likely to use them in independent clinical practice [16].…”
Section: Discussionmentioning
confidence: 99%